Antibiotic Appropriateness on Mondays vs. Fridays: Empiric Treatment of Simple Cystitis in the Emergency Department - LeBron, Kira A.; Bielawski, Adrienne; Popiel , Patrick; Shams , Setareh; Grimes, Cara L. (International Journal of Medical Students, 2024)
Background: The treatment of urinary tract infections (UTIs) has contributed to the rise of antibiotic resistance. Antibiotic appropriateness in the outpatient setting is lower than expected. We hypothesized that prescribing practices may vary based on the day of the week. We sought to determine the percentage of antibiotic prescriptions that met criteria for antibiotic appropriateness on Mondays vs. Fridays. Methods: This is a retrospective cohort study of adult females with simple cystitis presenting to the Emergency Department (ED) between 2019 and 2021. We defined antibiotic appropriateness based on the Infectious Diseases Society of America guidelines in conjunction with a regional outpatient UTI antibiogram. Each prescription was assessed for drug selection, dose, frequency, and duration. Categorical data is reported as counts (%) and compared with chi-square. Nonparametric continuous data is reported as median (range) and compared with Mann-Whitney. Results: 160 subjects were included: 80 came to the ED on a Monday and 80 on a Friday. Demographics were similar; except, more subjects had antibiotic allergies on Mondays. The number of appropriate antibiotic prescriptions was similar between Mondays and Fridays: 54 (68%) and 60 (75%), respectively (p=0.3). Overall, 44 subjects had an inappropriate duration of antibiotics and 14 subjects had an inappropriate antimicrobial prescribed, with no differences between Mondays and Fridays. Dose and frequency were always correct. In total, there were 46 (29%) antibiotics that failed to meet appropriateness criteria. Conclusions: There was no difference in antibiotic appropriateness between Mondays and Fridays; however, 29% of prescriptions did not meet criteria for appropriateness.